Prospecção e monitoramento informacional no contexto da inteligência competitiva em microempresas do ramo óptico da região de Marília - SP - Pacheco, Cíntia Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The contemporary global scenario significantly affects all segments of the society, particularly business. In this context, small-sized business noteworthy because they are responsible for the economy in a particular city or region and, therefore, becomes relevant their research because of its entrepreneurial character. However, few studies are implemented under the small-sized business aspects in terms of business competitiveness and the use of strategic information for decision making. Moreover, companies generally unaware of the methods, techniques and information and communication technologies (ICTs) to perform activities of information scanning and information mining, which enables to identify and track information, allowing decisionmaking more assertive with use of strategic information, which contributes to business competitiveness. This work aimed to analyze the formal and informal methods of information scanning and information mining, through a structured interview applied to small-sized business in the optical sector associated with the Associação Comercial e Industrial de Marília (ACIM) belonging to the Núcleo Especializado de Ópticas de Marília (NEOM). It had to be based on an information scanning and information mining model, as well as aspects related to information behavior that allowed us to understand how companies deal with information in their business, as well as issues relating to the future of companies, through the perception of future scenarios. The data analysis was performed using the method 'Content Analysis'. The results were presented in detail by analysis category and also synthetically by companies, in order to provide this latter case the profile of each NEOM company. We identified the key information needs and information sources used by managers, given its informal practice in scanning and mining... (Complete abstract click electronic access below)

O cenário contemporâneo globalizado afeta substancialmente todos os segmentos da sociedade, especialmente as empresas. Nesse contexto, as microempresas merecem destaque, pois são responsáveis pela economia de uma determinada cidade ou região e, portanto, torna-se relevante sua investigação devido ao seu caráter empreendedor. No entanto, poucas pesquisas são aplicadas no âmbito das microempresas no que tange aos aspectos da competitividade empresarial e do uso de informações estratégicas para a tomada de decisão. Além disso, as empresas geralmente desconhecem os métodos, as técnicas e as tecnologias de informação e comunicação (TICs) para a realização das atividades de prospecção e monitoramento informacional, as quais possibilitam identificar e acompanhar informações, permitindo uma tomada de decisão mais assertiva com a utilização de informação estratégica, o que contribui para a competitividade empresarial. Dessa forma, objetivou-se analisar os métodos formais e informais de prospecção e monitoramento informacional, por meio de um roteiro de entrevista aplicado às microempresas do ramo óptico associadas à Associação Comercial e Industrial de Marília (ACIM) pertencentes ao Núcleo Especializado de Ópticas de Marília (NEOM). Teve-se como base um modelo de prospecção e monitoramento informacional, bem como aspectos relacionados ao comportamento informacional que permitiram compreender como as empresas lidam com informação em seus negócios, e também questões inerentes ao futuro das empresas, por meio da percepção de cenários futuros. A análise dos dados foi realizada utilizando-se do método ‘Análise de Conteúdo’. Os resultados foram apresentados detalhadamente por categorias de análise e também sinteticamente por empresas, visando nesse último caso fornecer o perfil de cada...
Keywords: Inteligência competitiva (Administração); Concorrencia administrativa; Microempresas - Ramo óptico - Região de Marília (SP); Gestão da informação; Monitoramento informacional; Prospecção informacional; Competitividade empresarial; Information Scanning; Information Mining; Competitive Intelligence; Business Competitiveness; Information Management; Small-Sized Business; Optical Sector